Climate impacts on flood and coastal erosion infrastructure. Issue 2 (June 2015) - Sayers, Paul; Walsh, Claire; Dawson, Richard
Abstract : Climate change can affect the performance of flood and coastal erosion risk management infrastructure (FCERMi) through a number of mechanisms. This review highlights that while it is well known that climate change can influence the performance of FCERMi in a number of ways, there is extremely poor quantitative understanding of the physical processes of time-dependent deterioration and the impact of changing loads (and the interactions between these) on the reliability of FCERMi. If FCERMi is to be more robust to future climate uncertainties, there is an urgent need for research to better understand these interactions in the long term. This must be coupled with an updated approach to design and management that considers changes in extreme values, storm sequencing, spatial coherence, or more subtle impacts from changes in temperature, solar radiation and combinatorial affects.